Global recessions - M. Ayhan Kose; Naotaka Sugawara; Marco E. Terrones (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
The world economy has experienced four global recessions over the past seven decades: in 1975, 1982, 1991, and 2009. During each of these episodes, annual real per capita global GDP contracted, and this contraction was accompanied by weakening of other key indicators of global economic activity. The global recessions were highly synchronized internationally, with severe economic and financial disruptions in many countries around the world. The 2009 global recession, set off by the global financial crisis, was by far the deepest and most synchronized of the four recessions. As the epicenter of the crisis, advanced economies felt the brunt of the recession. The subsequent expansion has been the weakest in the post-war period in advanced economies as many of them have struggled to overcome the legacies of the crisis. In contrast, most emerging market and developing economies weathered the 2009 global recession relatively well and delivered a stronger recovery than after previous global recessions.
Keywords: E32; F44; N10; O47; 330; Global economy; global expansion; global recession; global recovery; synchronization of cycles; financial markets; real activity